Himalayan face-off: Chinese Assertion and the Indian Riposte - "Gupta, Shishir" (Gurgaon, 2014)
In April 2013, Indian troops sighted an advance patrol of the Chinese People's Liberation Army (PLA) 19 km deep within Indian territory, a considerable distance from the Line of Actual Control, the de facto border claim line that was drawn up after the 1962 war between the two countries - a war that still traumatizes the mind of India's political and military establishment.Protracted negotiations led to the withdrawal of the Chinese troops but the incursion laid bare the intent of the world's largest standing army. Despite recent advances in the bilateral relationship, highlighted by the nearly $70 billion trade between the two countries, China continues to regard Indian interests as secondary and India as a regional adversary. In this breakthrough work, seasoned journalist and author of the bestselling Indian Mujahideen Shishir Gupta details the various advances made by Beijing, particularly the PLA, in encircling India and stifling the latter's bid to break out as an aspiring superpower. Gupta discusses Indian political, diplomatic and military responses to China's assertion in the subcontinent and beyond and the various course corrections India must undergo in its foreign and defence policies to counter China's might and influence on matters of India's national security. In describing how India must realize and counter China's clout over its friends and enemies if it is to achieve superpower status, Gupta sheds new light on Indo-China relations. The Himalayan Face-Off: Chinese Assertion and the Indian Riposte is an important reminder of the realigned geopolitics of the modern world, where the two most populous nations on the planet are essentially battling each other over their share of the global pie - sometimes on the world's highest battlegrounds.
Keywords: China-India-Military relations